Inside Front Cover: Emerging theranostic applications of carbon dots and its variants (View 2/2022). Issue 2 (21st March 2022) - Ray, Priyanka; Moitra, Parikshit; Pan, Dipanjan
Abstract : In article number 20200089, Dipanjan Pan and co‐wokers provide a comprehensive account on carbon dots (CDs), their unique photophysical properties and application in interdisciplinary areas. The CDs find a wide range of applications including biosensing, imaging, drug delivery, voltaic cells and theranostics. Especially in this cover, we highlighted a unique class of carbon dots those are passivated with electron‐accepting and electron‐donating molecules. These nanoparticles exhibit inter‐particulate interaction and self‐assemble into toroidal‐like morphologies.